The Influence of Crowdedness and Brand Experience to Increase the Customer Loyalty in a Spicy Noodle Restaurant - Rahma, Tazkiyah Hasti Paramita; Setiawan, Budi; Isaskar, Riyanti; Wahyuningtyas, Agustina Shinta Hartati (Jurnal Social Economic of Agriculture, 2024)
Malang City is known as a tourist and student city that experiences population growth every year causing crowdedness phenomenon in several destinations, one of which is at Mie Gacoan restaurant. Crowdedness is a part of environmental psychology that can influence customers to buy and visit the restaurant in the future. Brand experience is another component that can influence customer loyalty in the long term, because loyalty is often considered a behavior that is reflected by customers and is considered a form of a way to maintain the existence of a restaurant and achieve a competitive advantage. This research aims to find out how crowding and brand experience influence brand image to increase customer loyalty through word of mouth. The respondents for this research were 250 people using purposive sampling and using a questionnaire. The method used is partial least squares "“ structural equation modeling (PLS-SEM). The results show that crowding has a positive and significant effect on brand image, brand experience has a positive and significant effect on brand image and word of mouth, brand image has a positive and significant effect on word of mouth, and word of mouth has a positive and significant effect on customer loyalty.